A Method for Detecting and Blocking Instant Messaging Software - Hao Zhang; Guangli Xu; Jiongzhao Yang; Jianmin Li (Institute of Advanced Engineering and Science, 2013)
Instant messaging software, as a convenient network communication tool, is becoming more and more popular. At the same time, it also brings risks in security of local area network (LAN). Through studying in typical instant messaging software and detected by the combination of misuse detection and protocol analysis, an architecture of detecting and blocking mechanism of instant messaging software is proposed in this paper and its prototype system is achieved on Windows platform. This new system effectively solves the problems that the efficiency of traditional firewall application layer data filtering is low and the firewall cannot dynamically adjust the filtering rules, providing a good application value for the protection of the security of local area network. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3394